The real effects of institutional spatial concentration. Issue 4 (22nd March 2021) - Huang, Xiaoran; Qiao, Zheng; Zhang, Lei
Abstract: We present evidence that spatially concentrated institutional investors enhance corporate innovation. These investors can coordinate more efficiently, leading to lower turnover of the holding firms' stocks and more diversified portfolios, which enables the holding firms to increases corporate risk‐taking and focus more on long‐term investments. Consistent with this argument, we find that firms with spatially concentrated investors take higher risk, invest more heavily in innovative projects, generate more patents, and have more patent citations. Our results are robust to using instrumental variables and the introduction of a new airline route as an exogenous shock to spatial concentration among institutional investors.